Effects of different carbohydrate sources on fructan metabolism in plants of Chrysolaena obovata grown in vitro - Trevisan, Flavio; Oliveira, Vanessa Fatima; Carvalho, Maria Angela M.; Gaspar, Marília G. (Frontiers in Plant Science, 2015)
Chrysolaena obovata (Less.) Dematt., previously named Vernonia herbacea, is an Asteraceae native to the Cerrado which accumulates about 80% of the rhizophore dry mass as inulin-type fructans. Considering its high inulin production and the wide application of fructans, a protocol for C. obovata in vitro culture was recently established. Carbohydrates are essential for in vitro growth and development of plants and can also act as signaling molecules involved in cellular adjustments and metabolic regulation. This work aimed to evaluate the effect of different sources of carbohydrate on fructan metabolism in plants grown in vitro. For this purpose, C. obovata plants cultivated in vitro were submitted to carbon deprivation and transferred to MS medium supplemented with sucrose, glucose or fructose. Following, their fructan composition and activity and expression of genes encoding enzymes for fructan synthesis (1-SST and 1-FFT) and degradation (1-FEH) were evaluated. For qRT-PCR analysis partial cDNA sequences encoding two different C. obovata genes, 1-SST and 1-FFT, were isolated. As expected, C. obovata sequences showed highest sequence identity to other Asteraceae 1-SST and 1-FFT, than to Poaceae related proteins. A carbon deficit treatment stimulated the transcription of the gene 1-FEH and inhibited 1-SST and 1-FFT and carbohydrate supplementation promoted reversal of the expression profile of these genes. With the exception of 1-FFT, a positive correlation between enzyme activity and gene expression was observed. The overall results indicate that sucrose, fructose and glucose act similarly on fructan metabolism and that 1-FEH and 1-SST are transcriptionally regulated by sugar in this species. Cultivation of plants in increasing sucrose concentrations stimulated synthesis and inhibited fructan mobilization, and induced a distinct pattern of enzyme activity for 1-SST and 1-FFT, indicating the existence of a mechanism for differential regulation between them.